The Urgence of Developing Civic Education E-Book Based On Mind Mapping For Students And Lecturers - Mariyani Mariyani; Edwin Nurdiansyah; Aulia Novhemy Dhita SBK; Ulfatul Hasanah; Ernawati Ernawati; Dini Herdianti (Universitas of Muhammadiyah Makassar, 2022)
This study aims to determine the urgency of developing mind mapping-based civic education e-books for students and lecturers. This research is a research method This research method is research and development (RnD) which ultimately produces a product and tests the level of product effectiveness. The subjects of this research are 54 first semester students in the 2021/2022 academic year who are taking civic education courses and 10 lecturers who are lecturers of civic education courses. The sampling technique used random sampling. The research activity was carried out at Sriwijaya University, South Sumatra. The data collection technique used is filling out questionnaires and documentation. The results of the study showed that the development of mind mapping-based civic education e-books was needed to facilitate student learning, both with educators and independently. E-books are teaching materials that are packaged digitally in the form of files and schematics according to the Lesson Plan. The existence of mind mapping in e-books will help students and lecturers to achieve fun and creative civic education learning goals.